2011
DOI: 10.1016/j.jacc.2010.08.626
|View full text |Cite
|
Sign up to set email alerts
|

3-Year Follow-Up of Patients With Coronary Artery Spasm as Cause of Acute Coronary Syndrome

Abstract: ACS patients without culprit lesion and proof of coronary spasm have an excellent prognosis for survival and coronary events after 3 years compared with patients with obstructive ACS. However, persistent angina represents a challenging problem in these patients, leading in some cases to repeated coronary angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(42 citation statements)
references
References 22 publications
1
40
0
1
Order By: Relevance
“…However, prolonged spasm is commonly associated with other emergency conditions, including acute coronary syndrome and life-threatening arrhythmias [16,17]. Thus, early accurate diagnosis and further VSA management is important.…”
Section: Discussionmentioning
confidence: 99%
“…However, prolonged spasm is commonly associated with other emergency conditions, including acute coronary syndrome and life-threatening arrhythmias [16,17]. Thus, early accurate diagnosis and further VSA management is important.…”
Section: Discussionmentioning
confidence: 99%
“…ACS patients with coronary spasm and nonobstructive coronary artery disease have a favorable prognosis for survival and coronary events 11, 12. In the Coronary Artery Spasm in Patients with Acute Coronary Syndrome study, nonobstructive ACS patients with documented coronary spasm showed no cardiac death or nonfatal MI during a 3‐year follow‐up 11.…”
Section: Discussionmentioning
confidence: 99%
“…ACS patients with coronary spasm and nonobstructive coronary artery disease have a favorable prognosis for survival and coronary events 11, 12. In the Coronary Artery Spasm in Patients with Acute Coronary Syndrome study, nonobstructive ACS patients with documented coronary spasm showed no cardiac death or nonfatal MI during a 3‐year follow‐up 11. In a Japanese population, cardiovascular events occurred in 15 (4.7%) patients with coronary artery spasm, including 1 (0.3%) patient with cardiovascular death and 4 (1.3%) patients with MI during a mean follow‐up duration of 20 months 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 3 years of the CASPAR study follow-up, ACS patients without culprit lesions were seen to have an excellent prognosis for survival and coronary events compared with patients with obstructive ACS. However, persistent angina represents a challenging problem in these patients, leading to repeated coronary angiography in some cases [5]. Data on prognosis in ACS patients without culprit lesions in China are sparse.…”
Section: Introductionmentioning
confidence: 99%